Barriers to antiretroviral therapy adherence in developed countries: a qualitative synthesis to develop a conceptual framework for a new patient-reported outcome measure. (14th December 2018) - Engler, Kim; Lènàrt, Andras; Lessard, David; Toupin, Isabelle; Lebouché, Bertrand
ABSTRACT: Suboptimal adherence to antiretroviral therapy (ART) remains common. Patient-centered tools are needed to comprehensively assess adherence barriers in HIV clinical practice. Thus, we conducted a research synthesis to produce a conceptual framework for a new patient-reported outcome measure (PRO) for use in routine HIV care in Canada and France. A PRO's conceptual framework graphically represents the concepts to be measured and the potential relationships between them. Towards ensuring the framework's relevance to the target populations' concerns, qualitative studies with HIV-positive adults on barriers to ART adherence in developed countries were synthesized with thematic analysis, attending to the cross-study prevalence and interrelationships of barrier themes. In March 2016, searches within Medline, PsychINFO, and Embase produced 5, 284 records. Two reviewers determined the final sample ( n = 41). Analysis generated three levels of ART adherence barrier themes. Twenty Level 2 themes and their component subthemes (Level 3) were organized into 6 higher-order themes (Level 1): Cognitive and emotional aspects (100% of studies contributing content -prevalence), Lifestyle factors (95%), Social and material context (95%), Characteristics of ART (90%), Health experience and state (73%), and Healthcare services and system (66%). As to interrelationships, study authors articulated relationships between all higher-order themes (Level 3). Linkages between Level 2 barrier themes showed great variability, from 21% to 95%. Overall, this synthesis contributes an exceptionally detailed conceptual framework and report of ART adherence barriers, applicable to a wide range of PLHIV. It suggests that a key to understanding many barriers is through their interconnections. It also identifies gaps in barrier research. Concerning the new PRO's development, comprehensiveness will need to be weighed against other concerns (e.g., respondent burden) and the provision of barrier-specific guidance for clinically addressing its scores seems essential.